2013
DOI: 10.1371/journal.pone.0057200
|View full text |Cite
|
Sign up to set email alerts
|

The Terpolymer Produced by Azotobacter Chroococcum 7B: Effect of Surface Properties on Cell Attachment

Abstract: The copolymerization of poly(3-hydroxybutyrate) (PHB) is a promising trend in bioengineering to improve biomedical properties, e.g. biocompatibility, of this biodegradable polymer. We used strain Azotobacter chroococcum 7B, an effective producer of PHB, for biosynthesis of not only homopolymer and its main copolymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHB-HV), but also novel terpolymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate)-poly(ethylene glycol) (PHB-HV-PEG), using sucrose as the primary carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
0
18
0
3
Order By: Relevance
“…The PHBV was synthesized from the Azotobacter chroococcum strain 7B by the precursor feeding approach as previously described . Briefly, the culture was grown in shaker flasks at 30 °C in Burk's medium with 50 m M sucrose as primary carbon source supplemented with 20 m M sodium valerate (to produce the PHBV copolymer) and 50 m M sodium acetate (to regulate the PHBV molecular weight).…”
Section: Methodsmentioning
confidence: 99%
“…The PHBV was synthesized from the Azotobacter chroococcum strain 7B by the precursor feeding approach as previously described . Briefly, the culture was grown in shaker flasks at 30 °C in Burk's medium with 50 m M sucrose as primary carbon source supplemented with 20 m M sodium valerate (to produce the PHBV copolymer) and 50 m M sodium acetate (to regulate the PHBV molecular weight).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research findings into PHA/PEG biocompatibility have been contradictory. Some of the authors reported that copolymerization or blending with PEG improved PHA biocompatibility while others argued that the presence of PEG decreased PHA biocompatibility …”
Section: Resultsmentioning
confidence: 99%
“…Количество живых клеток определяли по стандартной калибровочной прямой для теста ХТТ. Эти данные представлены как характеристика биосовместимости in vitro полимерных плёнок [6][7][8].…”
Section: изучение роста клеток In Vitro на подложках на основе пгбunclassified